Tetramodal therapy with transurethral resection followed by chemoradiation in combination with hyperthermia for muscle-invasive bladder cancer: early results of a multicenter phase IIB study. (31st December 2022) - Riesterer, Oliver; Ademaj, Adela; Puric, Emsad; Eberle, Brigitte; Beck, Marcus; Gomez, Silvia; Marder, Dietmar; Oberacker, Eva; Rogers, Susanne; Hälg, Roger A.; Kern, Thomas; Schwenne, Sonja; et al.
Abstract: Background: Transurethral resection of bladder tumor (TUR-BT) followed by chemoradiation (CRT) is a valid treatment option for patients with muscle-invasive bladder cancer (MIBC). This study aimed to investigate the efficacy of a tetramodal approach with additional regional hyperthermia (RHT). Methods: Patients with stages T2–4 MIBC were recruited at two institutions. Treatment consisted of TUR-BT followed by radiotherapy at doses of 57–58.2 Gy with concurrent weekly platinum-based chemotherapy and weekly deep RHT (41–43 °C, 60 min) within two hours of radiotherapy. The primary endpoint was a complete response six weeks after the end of treatment. Further endpoints were cystectomy-free rate, progression-free survival (PFS), local recurrence-free survival (LRFS), overall survival (OS) and toxicity. Quality of life (QoL) was assessed at follow-up using the EORTC-QLQ-C30 and QLQ-BM30 questionnaires. Due to slow accrual, an interim analysis was performed after the first stage of the two-stage design. Results: Altogether 27 patients were included in the first stage, of these 21 patients with a median age of 73 years were assessable. The complete response rate of evaluable patients six weeks after therapy was 93%. The 2-year cystectomy-free rate, PFS, LRFS and OS rates were 95%, 76%, 81% and 86%, respectively. Tetramodal treatment was well tolerated with acute and late G3–4 toxicities of 10% and 13%, respectively, and a tendency to improve symptom-related quality of life (QoL) one year after therapy. Conclusion: Tetramodal therapy of T2–T4 MIBC is promising with excellent local response, moderate toxicity and good QoL. This study deserves continuation into the second stage.